2011
DOI: 10.1038/nature10176
|View full text |Cite
|
Sign up to set email alerts
|

Increased soil emissions of potent greenhouse gases under increased atmospheric CO2

Abstract: Increasing concentrations of atmospheric carbon dioxide (CO2) can affect biotic and abiotic conditions in soil, such as microbial activity and water content1, 2. In turn, these changes might be expected to alter the production and consumption of the important greenhouse gases nitrous oxide (N2O) and methane (CH4) (refs 2, 3). However, studies on fluxes of N2O and CH4 from soil under increased atmospheric CO2 have not been quantitatively synthesized. Here we show, using meta-analysis, that increased CO2 (rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
271
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 448 publications
(290 citation statements)
references
References 23 publications
16
271
0
3
Order By: Relevance
“…In conclusion, our data support the hypothesis that increased plant productivity will increase CH 4 emissions from wetlands (van Groenigen et al 2011). Productivity increased as the result of genotypic variability within a single species, and as the result of increased resource availability (i.e.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In conclusion, our data support the hypothesis that increased plant productivity will increase CH 4 emissions from wetlands (van Groenigen et al 2011). Productivity increased as the result of genotypic variability within a single species, and as the result of increased resource availability (i.e.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have reported that elevated CO 2 alone can increase wetland CH 4 emissions (reviewed in van Groenigen et al 2011). In the present experiment, elevated CO 2 stimulated CH 4 emissions only in combination with added N, providing an example of an interaction among global change factors that must be considered in order to forecast changes in emissions of this greenhouse gas.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…139 What the outcomes of this increase in greenhouse gases will be is the unanswered question. 140,141 Regardless, action should be taken and this requires the adsorption of these gases. Graphene, like other carbon-based materials, is light and cheap to produce in comparison to other solid state gas adsorbent materials.…”
Section: Gas Adsorption and Gas Phase Separationmentioning
confidence: 99%
“…However, this finding underestimates the contribution of methane to the climate problem, because its interaction with aerosols increases its activity; also, its relatively short residence time in the atmosphere makes it especially sensitive to corrective intervention (8). There is also a synergistic effect, because increased amounts of atmospheric CO 2 are predicted to stimulate methane emissions from rice paddies (9). Because the soil methanogens quickly become dormant when the paddies are drained, emissions can be reduced by decreasing the amount of time that the paddies are submerged.…”
mentioning
confidence: 99%